Effect of the incorporation of a fermented rooibos (Aspalathus linearis) extract in the manufacturing of rabbit meat patties on their physical, chemical, and sensory quality during refrigerated storage. (July 2019) - Cullere, Marco; Tasoniero, Giulia; Secci, Giulia; Parisi, Giuliana; Smit, Paula; Hoffman, Louwrens Christiaan; Dalle Zotte, Antonella
Abstract: In the present study, rabbit meat patties were formulated with increasing incorporation levels of a fermented rooibos extract ( Aspalathus linearis ; R): Control (C), R1, R2 and R3 (0, 0.5, 1, 2% w/w R inclusion, respectively). Meat patties were subjected to a 7-day refrigerated storage trial, simulating retail display conditions. At day 0, 1, 3 and 6 of storage, patties drip loss, pH, L*a*b* colour traits (raw patties) and peroxide value (cooked patties) were analysed; at days 0 and 6, total volatile basic nitrogen (raw patties), fatty acid profile and sensory traits (cooked patties) were analysed. Increasing R incorporation levels lowered pH values of rabbit meat patties and increased their redness and yellowness indexes compared to the C group ( P < 0.0001). R-treated cooked patties were protected from lipid oxidation compared to C ones ( P < 0.0001), and this status was maintained up to the end of the trial. R1 rabbit meat patties showed sensory traits comparable to the C group, whereas R2 and R3 treatments provided negative outcomes. Based on the above-mentioned findings, rooibos can be considered a promising natural additive in the manufacturing of rabbit meat patties, up to the 0.5% incorporation level. Highlights: Rooibos extract was tested as natural antioxidant in rabbit meat patties. Different inclusion levels on meat physico-chemical-sensory traits were tested. All rooibos levels improved the oxidative status of rabbit meat patties. The 0.5% rooibos inclusion level ensured satisfactory patties sensory traits. Rooibos confirmed to be a promising natural antioxidant for meat products.